2020
DOI: 10.1097/bpo.0000000000001412
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of EOSQ-24 and SRS-22 Scores in Congenital Scoliosis: A Preliminary Study

Abstract: Background: The 24-item Early-Onset Scoliosis Questionnaire (EOSQ-24) and 22-item Scoliosis Research Society (SRS-22) questionnaire measure health-related quality of life in patients with scoliosis. The EOSQ-24 has been recently validated in early-onset scoliosis (EOS), including congenital scoliosis (CS). The SRS-22 has been validated in idiopathic scoliosis. The EOSQ-24 is completed by the caregiver and the SRS-22 is completed by the patient. The primary purpose of this study was to compare the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…The difficulties encountered in this evaluation include their young age, and therefore, we asked their parents to fulfill these questionnaires. 22 In accordance with our hypothesis, the long immobilization (cast 6 weeks and brace 3 months) decreased their QoL at 6 months, although the function domain of the SRS-24 improved further to final follow-up. Future research needs to address ways to decrease the incidence of skin-related complications.…”
Section: Comparison With Previous Datasupporting
confidence: 86%
See 2 more Smart Citations
“…The difficulties encountered in this evaluation include their young age, and therefore, we asked their parents to fulfill these questionnaires. 22 In accordance with our hypothesis, the long immobilization (cast 6 weeks and brace 3 months) decreased their QoL at 6 months, although the function domain of the SRS-24 improved further to final follow-up. Future research needs to address ways to decrease the incidence of skin-related complications.…”
Section: Comparison With Previous Datasupporting
confidence: 86%
“…The SRS-24 questionnaire has not been used previously in this patient group, but SRS-22, the modification of this original questionnaire, has recently shown a good correlation with the EOSQ-24 questionnaire in this patient population. 22…”
Section: Srs-24 Outcome Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…The original version of the SRS-22 was developed for adolescents who had idiopathic scoliosis [ 23 ]. However, recently, Li et al [ 28 ] conducted a study on patients with congenital scoliosis and found that except for the satisfaction domain, there was a strong correlation between all the sub-domains of the SRS-22 and EOSQ-24. Therefore, SRS-22 is a good instrument for investigating the convergent validity of the EOSQ-24.…”
Section: Discussionmentioning
confidence: 99%
“…Although the SRS-22 has also been used to assess the HRQoL of patients with congenital scoliosis 92) , this questionnaire has several limitations and poorly reflects other important aspects of a patient's life. In EOS, factors such as pulmonary function, fatigue, and parental burden are arguably more essential factors to evaluate than for other types of adolescent or adult scoliosis.…”
Section: Discussionmentioning
confidence: 99%